TEACHING ENGLISH VOCABULARY TO ELEMENTARY SCHOOL-AGED CHILDREN THROUGH A MODIFIED HOP-SCOTCH GAME NAMED PORTEK (PORTABLE ENGKLEK) (English Education Journal, 2012)
Bahasa Inggris mempunyai peranan yang sangat penting sebagai konektor pada era sekarang dimana sangat menuntut masyarakat untuk berpikir secara global tanpa meninggalkan budaya lokal. Masyarakat Indonesia membutuhkan cara untuk memperkenalkan, mengajar, dan menggunakan Bahasa Inggris mulai dari anak-anak sampai dewasa. Pemilihan materi harus disesuaikan dengan tingkat dan pengenalankosa kata. Guru membutuhkan media untuk mengajar kosa kata kepada anak-anak untuk mencapai tujuan yang sudah ditentukan,disamping itu siswa juga harus dimotivasi  untuk menyukai Bahasa Inggris. Dalam mengajar kosakata guru harus menggunakan sesuatu yang dekat dengan siswa dalam mengajarkan kosakata. Indonesia kaya akan permainan-permainan tradisional, Jawa Tengah misalnya yang memiliki betengan untuk mempererat kerja tim, dan engklek untuk melatih jiwa dan raga. Engklek dipilih sebagai media pembelajaran kosakata setelah dimodifikasi lebih modern  menjadi portek (portable engklek). Pengajaran Bahasa Inggris menggunakan engklek mempunyai 2 tujuan yaitu menciptakan situasi pembelajaran yang menyenangken dan melestarikan warisan budaya kepada generasi selanjutnya.It is the era when everyone needs to think globally but be aware with their area locally.  The people need to be connected with the worldwide.  Here, English as an international language takes important capacity as the connector, including in Indonesia.  Indonesians (from the government to the people) need treatments to introduce, teach, and use English to the learners, the young or adult.  Chosen English materials depend on the grade, and introducing vocabulary is an obligatory.  Teachers need to use media to teach English vocabulary to young learners in order to reach the goal of English teaching learning process, including to elementary school-aged children.  They need to be motivated and enhanced their intrinsic motivation, so they love English by themselves.  Teachers may use something that is close to the young learners in teaching English vocabulary.  Indonesia country has some more beautiful, wise traditional games.  In Central Java, there are games to build team-work through betengan, exercising the body and mind through engklek, etc. One of them can be used as the media in teaching English vocabulary to young learners.  Engklek is chosen.  Here, the original concept of engklek is modified into the modern one namely Portek (Portable engklek).  Teaching English to young learners through Portek as the medium has at least 2 goals: teaching foreign language in interesting situation, and perpetuating our cultural heritage to the next generation.